Kontribusi Media Buku Harian dalam Pengembangan Budaya Literasi Menulis bagi Siswa Sekolah Dasar - Priyanti Priyanti; Novan Ardy Wiyani; Mukti Amini (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
Indonesia is experiencing a literacy crisis. The government also issued a policy that regulates that every school implements the School Literacy Movement. One of the efforts made to carry out this movement is to use a diary as a medium to strengthen the literacy skills of elementary school students. This study aims to describe and analyze the contribution of the use of a diary in developing a writing literacy culture at SD Negeri 1 Karanganyar Purbalingga. This research is a type of phenomenological research with a qualitative approach. Data were collected by interview, observation and documentation, then analyzed through the stages of data reduction, data display and verification. The results showed that the use of a diary in developing writing literacy culture at SD Negeri 1 Karangnyar was carried out through three activities: the use of diary media in habituation, development, and learning. These activities are carried out through three stages: preparation, implementation, and assessment. Writing literacy applied with a diary is intended for students in grades 3-6. Using a diary in writing literacy carried out in habituation, development and learning activities has made a real contribution to developing a writing literacy culture.